Aplikasi Varietas Dan Dosis Pupuk Npk Terhadap Produksi Jagung( Zea Mays L. ) - Meiyana Hikmawati (Universitas Merdeka Madiun, 2019)
The objectives of this research is Application of variety and NPK fertilizer dosage on the yield of corn (Zea mays L). The method of the research use factorial design based on the Randomized Block Design with two factors of treatment. The first factor was variety : (V1) Pioner, (V2) NK 33, (V3) Pertiwi and second factor was NPK fertilizer dosage : (P0) without fertilizer, (P1) NPK fertilizer dosage 50 g/plot, (P2) NPK fertilizer dosage 100 g/plot, (P3) NPK fertilizer dosage 150 g/plot and each kombination of treatment three times replicated.The result of the research : (1) There was interaction between variety and NPK fertilizer dosage on the parameters of the weight of dry cob per plant . (2) The highest yield was treatment (V3) Pertiwi and (P3) NPK fertilizer dosage 150 g/plotfor all parameters. (3) The highestÂ yield was treatment combination V3 P3 (variety pioner and NPK fertilizer dosage 150 g/plot) providing the best harvest.